Factory eco-efficiency modelling: framework development and testing - Davé, Aanand; Ball, Peter D.; Salonitis, Konstantinos; Astfalck, C. (Future Technology Press, 2015)
Eco-efficiency is becoming an increasingly important organisational performance measure. Its indicators are regularly used alongside productivity, cost, quality, health and safety in operations and corporate social responsibility reporting. The purpose of this paper is to show an eco-efficiency modelling framework, and its application in the case of an automotive manufacturer. The framework composes, models and analyses resource and production data. Focus on energy, water distributions and material transformations in manufacturing, utility and facility assets are used to analyse eco-efficiency. Resources are examined in respect to three data granularity factors: subdivision, pulse, and magnitude. Models are linked with performance indicators to assess asset eco-efficiency. This work contributes to industrial sustainability literature by introducing a modelling framework that links with data granularity and eco-efficiency indicators.